Radical philosophical concepts as a resource for doctrinal renewal of criminal law - Туляков, Вячеслав Олексійович; Туляков, В. О.; Tuliakov, Viacheslav O. (SSRN, 2025)
This article analyzes the heuristic potential of radical philosophical concepts for the doctrinal renewal of criminal law. The expediency of a paradigmatic approach is substantiated, in which doctrine is considered an independent source of criminal law. Special attention is paid to the possibility of reconfiguring criminal-legal thinking, taking into account transgressive, postsecular, and activity-based approaches. Modern criminal law increasingly encounters borderline situations that do not fit within the framework of positivist thinking. This is why interest is growing in radical philosophical concepts as a potential resource for doctrinal renewal of criminal law paradigms. Such an approach allows not only for the renewal of the norm, but also for the rethinking of normative rationality itself. In this context, an integrative analysis of the ideas of Georges Bataille, Michel Foucault, Georgy Shchedrovitsky, as well as the conceptual approaches of Leon Petrażycki and
preprint
Tuliakov V. Radical philosophical concepts as a resource for doctrinal renewal of criminal law (May 21, 2025) / Viacheslav Tuliakov ; National University "Odesa Law Academy". (Препринт. Available at SSRN : https://ssrn.com/abstract=). - Режим доступу : https://ssrn.com/abstract=5262869 or http://dx.doi.org/10.2139/ssrn.5262869
Keywords: кримінальне право; доктрина; філософія; criminal law; philosophy; doctrine